The New Visibility of the Salafi Da’wah in the “Digital Space”: Fundamentalism and Political Identity in the Post Suharto - Ja'far, Ali (LPPM IAIN Kudus, 2023)
This paper investigates the new visibility of Salafist da’wah on the new media. The media such as cassette, bulletin, television and the digital made religious material and the agents be more visible in the secularized world. The basic inquiries is how the Salafi agent reforms their visibility in the post Suharto era and how it deals with their Islamism agenda in the media. Alongside that visibility has also revised the secular thesis on the privatization of religion it also marks the resurgence of religion globally. Through analysing the Islamic post in the social media content in Instagram and using a qualitative research (content analysis), this paper sees about the new visibility and rise of fundamentalism and the Salafi preaching in the digital space. This paper also finds that fundamentalism is a radical response to secularism, and modernization which originated from the colonial period. However, currently the fundamentalism is not in antagonistic relation with democratization, they embrace it as a medium to spread their idea widely and to shape their political identity. Indeed, in the “digital space” where any people could voice their ideas and accept limitless information, Salafi’s preachers also modify their preaching to be more casual look, friendly, attractive and inspirational yet the idea is still conservative. Such modification was taken to grabs more audience and to be more visible in the digital space. This research implies that Salafi da’wah was reforming its visibility, especially in the post Suharto era where Islam, politic and technology were intermingled relation.